Life after Fire for Understory Plant Community in Subtropical Chir Pine Forest of Garhwal Himalaya - Konsam, Bobbymoore; Phartyal, Shyam Singh; Kumar, Munesh; Todaria, Nagendra Prasad (Indian Forester, 2017)
Fire is believed to act as an environmental cue for regeneration of plant community in majority of the forest ecosystems encounter natural fire. However, the positive role of anthropogenic fire on regeneration ecology of understory vegetation in chir pine forest is doubtful. In this study, the effect of anthropogenic fire on regeneration was compared between burned and unburned sites of the Chir pine forest in Garhwal Himalaya. The result indicated that forest fire has no considerable impact on regeneration. Species richness and seedling density were higher in burned and unburned sites respectively, but both of these trends were non-significant. Shannon-Wiener Diversity index (H’) and Evenness (J’) were high in burned as compared to unburned sites. Plant species that were regenerated through resprouting after forest fire includes ethnomedicinal species, grasses/fodder species, and invasive species. However, the majority of species in burned sites were regenerated through seeds. It is concluded that fire can act as an important disturbance factor to some extent, but it failed to enhance significantly the regeneration potential of understory vegetation. Thus, the finding contradicts the traditional beliefs of local communities which perceived grass/fodder plants regenerate much vigorously after an intentional forest fire.